2D layered nanomaterials as fillers in polymer composite electrolytes for lithium batteries - Vijayakumar, Vidyanand; Ghosh, Meena; Asokan, Kiran; Sukumaran, Santhosh Babu; Kurungot, Sreekumar; Mindemark, Jonas; Brandell, Daniel; Winter, Martin; Nair, Jijeesh Ravi (Advanced Energy Materials, 2023)
Polymer composite electrolytes (PCEs), i.e., materials combining the disciplines of polymer chemistry, inorganic chemistry, and electrochemistry, have received tremendous attention within academia and industry for lithium-based battery applications. While PCEs often comprise 3D micro- or nanoparticles, this review thoroughly summarizes the prospects of 2D layered inorganic, organic, and hybrid nanomaterials as active (ion conductive) or passive (nonion conductive) fillers in PCEs. The synthetic inorganic nanofillers covered here include graphene oxide, boron nitride, transition metal chalcogenides, phosphorene, and MXenes. Furthermore, the use of naturally occurring 2D layered clay minerals, such as layered double hydroxides and silicates, in PCEs is also thoroughly detailed considering their impact on battery cell performance. Despite the dominance of 2D layered inorganic materials, their organic and hybrid counterparts, such as 2D covalent organic frameworks and 2D metal-organic frameworks are also identified as tuneable nanofillers for use in PCE. Hence, this review gives an overview of the plethora of options available for the selective development of both the 2D layered nanofillers and resulting PCEs, which can revolutionize the field of polymer-based solid-state electrolytes and their implementation in lithium and post-lithium batteries.
Keywords: 2D materials; clay minerals; covalent organic frameworks; metal-organic frameworks; MXene; polymer composite electrolyte; solid-state batteries